Personality problems of college students - J, Bharath Raj (Journal of All India Institute of Speech and Hearing, 1971)
Against the background of the increasing number of strikes, demonstrations, outbursts leading to damage of property, a serious study of the adjustment problems of college students is worth the trouble. A fall in the achievement standards has added to the situation. Thus a study of the personality problems of the college students would provide for one angle of viewing the whole problem of ’student unrest’—as there would be a number of Psychosocial variables related to the issue.